Diabetes mellitus educational intervention in patients at risk from a medical office. Nuevitas, 2020-2023 - Maigret Calderón Cruz; Julio Michel Arias Manganelly; Olenis Alicia Aldana Ramos; Lieter Ailed Vidal Rodríguez; Pedro Figueredo Guerra; Aned Hernández Clavijo (Medisur)
Foundation: diabetes mellitus has been considered by the World Health Organization a serious health problem to be solved throughout the world. Its prevention and educating about it is essential. Objective: to describe an educational intervention on type 2 diabetes mellitus results in patients with risk factors. Methods: intervention study, with a before and after design, which included 120 patients over 18 years of age with diabetes mellitus risk factors, belonging to Medical Office No. 6, in Nuevitas, Camagüey province. A survey was applied to measure the level of knowledge, before and after the educational intervention. The variables: age, educational level, knowledge about diabetes mellitus, risk factors and prevention were analyzed. Results: women, university education level and those over 60 years of age predominated. At the beginning of the study, around 75% of the participants showed fair or low knowledge about diabetes mellitus, risk factors and prevention. All of these parameters increased above 85% after the intervention. Conclusions: a notable increase in knowledge about diabetes mellitus, its risk factors and how to prevent it was achieved. These types of strategies, applicable from the primary level of care, imply a benefit in the prevention of this and other non-communicable diseases.